Affective interpersonal relationships and work performance according to sociodemographic variables of radio and television workers in Metropolitan Lima - Bejarano Paredes, Manuel (2020)
The present investigation studies interpersonal relationships and work performance in workers of three state-owned radio and television companies in Metropolitan Lima, the sample consisted of 90 workers (44% male and 56% female). For the data collection, the Labor Performance Behavior Questionnaire and the Scale of Affective Interpersonal Relationships at Work (SRIT) were used, it was identified through the Kolmogorov-Smirnov statistic that the data collected presented non-parametric characteristics so that Analysis of results was done using the Rho statistic of Spearman d U of Man Whitney and the statistician Kruskal-Wallis. The results indicated that there is no significant correlation between the interpersonal affective relationships and work performance, a more thorough analysis of its components yields a moderate relationship between them. Likewise, the comparison between affective interpersonal relationships and work performance, with sociodemographic variables did not show a significant relationship.